1982
DOI: 10.1111/j.1476-5381.1982.tb09194.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Melatonin on Sleep and Neurochemistry in the Rat

Abstract: The effects of intraperitoneally administered melatonin on sleep and brain neurochemistry in the rat were studied by use of EEG recording and standard fluorescence techniques. Melatonin, 10 mg/kg, reduced time to sleep onset and time spent awake but increased both slow wave and paradoxical sleep. Qualitatively similar but smaller effects were produced by a dose of 2.5 mg/kg. Neither dose of melatonin altered normal EEG patterns or disrupted normal sleep behaviour. Melatonin, 20 mg/kg, did not significantly alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 21 publications
2
36
0
Order By: Relevance
“…The doses used in the study show a comparable effect as the therapeutic dosages. Therefore, although melatonin is an effective hypnotic agent both in animals (17,18) and humans (19), these findings suggest that melatonin may not directly affect the hypnotic action of zaleplon.…”
Section: Discussionmentioning
confidence: 93%
“…The doses used in the study show a comparable effect as the therapeutic dosages. Therefore, although melatonin is an effective hypnotic agent both in animals (17,18) and humans (19), these findings suggest that melatonin may not directly affect the hypnotic action of zaleplon.…”
Section: Discussionmentioning
confidence: 93%
“…Animal studies have demonstrated that MLT reduces time to sleep onset and increases both NREMS and REMS (Holmes and Sugden, 1982;Mirmiran and Pevet, 1986), with both effects being blocked by the GABA A receptor antagonists flumazenil and picrotoxin (Wang et al, 2003a). Other studies showed little or no effect (Mailliet et al, 2001;Wang et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…Holmes and Sugden 65 reported that MLT reduces time to sleep onset and increases both SWS and PS. Others suggest that MLT is involved only in the control of PS regulation since the lesion of the pineal gland or inhibition of MLT synthesis using a β-adrenergic antagonist (propranolol) decreased PS during light and dark periods.…”
Section: Melatonin and Sleepmentioning
confidence: 99%